Determining the Location of Public Green Open Space (Case Study: Soreang Urban Area) - Muhammad Arief Setiawan; Tonny Judiantono; Saraswati (Jurnal Perencanaan Wilayah dan Kota, 2025)
The increasing urban population will have an impact on the declining quality of the environment. These problems include high air pollution, flooding, and decreased community productivity due to stress caused by limited social interaction space. This needs to be suppressed by the presence of green open spaces (RTH) where RTH is the lungs of the city, microclimate regulators, shade, oxygen producers, rainwater absorbers, animal habitat providers and others. However, RTH only lowers the temperature in the surrounding area and does not lower the temperature of the entire urban area. In addition, RTH has a limited service range. Seeing this phenomenon, there needs to be an explanation why the location of RTH must be one stretch or preferably partial/spread so that in its implementation it is right on target according to needs. This study uses a social and environmental approach. The social approach uses the variables of population and land/land ownership. The environmental approach uses the Urban Heat Island variable and the range of RTH services. These variables are then analyzed spatially using arcgis software. Based on the UHI variables, the range of RTH services, the location of built-up land, the results of the study show that in order for the benefits of RTH to be maximized, in determining the location of RTH, the location of RTH should be partial/spread and not one stretch.